2011
DOI: 10.1371/journal.pone.0019573
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Couples' Voluntary Counseling and Testing in Urban Rwanda and Zambia: A Cross-Sectional Household Survey

Abstract: BackgroundMost incident HIV infections in sub-Saharan Africa occur between cohabiting, discordant, heterosexual couples. Though couples' voluntary HIV counseling and testing (CVCT) is an effective, well-studied intervention in Africa, <1% of couples have been jointly tested.MethodsWe conducted cross-sectional household surveys in Kigali, Rwanda (n = 600) and Lusaka, Zambia (n = 603) to ascertain knowledge, perceptions, and barriers to use of CVCT.ResultsCompared to Lusaka, Kigali respondents were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 42 publications
5
43
1
Order By: Relevance
“…Opportunity for earlier detection, early initiation of treatment and care and risk reduction strategies provided by PITC services were perceived highly by most respondents. The benefits of VCT services have been documented elsewhere by Anderson et al (2008), Shorter et al (2009), Mukolo et al (2013) and Musheke et al (2013. They have also been observed as entry points into couple counseling and increased HIV sero-status disclosure among couples (Becker et al, 2010;Kelley et al, 2011;Njau et al, 2012). This observation therefore calls for health care providers to maintain high level of confidentiality and patient care and explore the opportunity for couple counseling and promote disclosure among couples.…”
Section: Discussionmentioning
confidence: 89%
“…Opportunity for earlier detection, early initiation of treatment and care and risk reduction strategies provided by PITC services were perceived highly by most respondents. The benefits of VCT services have been documented elsewhere by Anderson et al (2008), Shorter et al (2009), Mukolo et al (2013) and Musheke et al (2013. They have also been observed as entry points into couple counseling and increased HIV sero-status disclosure among couples (Becker et al, 2010;Kelley et al, 2011;Njau et al, 2012). This observation therefore calls for health care providers to maintain high level of confidentiality and patient care and explore the opportunity for couple counseling and promote disclosure among couples.…”
Section: Discussionmentioning
confidence: 89%
“…Knowledge of HIV discordancy is far lower in Zambia versus Rwanda, 41 and also low in South Africa. 28 As a result, many do not disclose their HIV test results to partners and husbands often assume that their wife's test result from ANC must be the same as their own.…”
Section: Discussionmentioning
confidence: 96%
“…A household survey in 2003 confirmed that though most adults wanted to be tested with their partners, many thought CVCT was available at public facilities (which was not yet the case), and only 25% knew CVCT reduced HIV transmission within marriage. 41 …”
Section: Introductionmentioning
confidence: 99%
“…The implications of the local conceptions of contagious disease in rural southern Zambia on postnatal care-seeking for newborns are evident: understandings about disease transmission and treatment by clinic staff prevented or delayed HIV-infected mothers from seeking postnatal care for their newborns. Stigma attached to this particular type of disease acquisition, which includes unexposed infants becoming ill from exposure to the effects of HIV medication used by other infants, will be a challenge in the effort to increase postnatal care utilization and reduce HIV progression (Kelley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%